Supplementation of Carrot (Daucus carrota) as Natural Source of Beta-carotene prepared by Several Methods in Feed to Increase Blue Colour of Freshwater Crayfish Red Claw (Cherax quadricarinatus) - SatyantiniWoro H.; MubarakA. Shofy; MuktiA. Taufiq; C, Ninin (Jurnal Akuakultur Indonesia, 2012)
Red claw (Cherax quadricarinatus) is one kind of freshwater crayfish that can cultured as consumption or ornamental fish commodities. The colour of body was important character for performance of red claw as ornamental fish commodity. Red claw with blue body colour is more expensive than brown. The purpose of this experiment was to know the influence addition of carrot with several methods in feed on blue colour of freshwater crayfish red claw and which was the best preparation method to increase blue colour of freshwater crayfish red claw. The experiment used Completely Randomized Design with four treatments: A (control), B (extract), C (juice) and D (shreeded) of carrot with 45 ppm dose and five time replicates. Data was analysed with Kruskal-Wallis and continued with Z test. Result of the experiment was showed that addition of carrot as natural source of beta-carotene with several preparation in feed increase significantly (P<0.05) the blue colour on cheliped and chepalothorax until telson of red claw. Treatment D (shreeded) was given higher scoring of blue colour on cheliped and cephalothorax until telson, i.e. 2.82 and 2.54, respectively. Keywords: freshwater crayfish, colour of red claw, carrot, beta-carotene ABSTRAK Red claw (Cherax quadricarinatus) adalah salah satu jenis lobster air tawar yang dapat dibudidayakan sebagai komoditas konsumsi maupun hias. Sebagai komoditas ikan hias, warna tubuh merupakan karakter penting untuk menunjang penampilan red claw. Red claw ukuran konsumsi yang memiliki warna biru akan memiliki nilai jual yang lebih tinggi daripada red claw berwarna coklat. Tujuan penelitian ini untuk mengetahui pengaruh penambahan wortel sebagai sumber beta karoten alami dengan beberapa metoda pengolahan pada pakan terhadap peningkatan warna biru lobster red claw. Penelitian menggunakan Rancangan Acak Lengkap dengan 4 perlakuan : A (kontrol), B (ekstrak), C (jus) dan D (serutan) wortel dengan menggunakan dosis 45 ppm beta karoten dan ulangan 5 kali. Data dianalisis dengan uji Kruskal-Wallis dan dilanjutkan dengan uji Z. Hasil penelitian menunjukkan bahwa penambahan wortel sebagai sumber beta karoten alami dengan beberapa metode pengolahan (ekstrak, jus dan serutan) pada pakan memberikan hasil berbeda nyata (P<0,05) pada peningkatan warna biru pada capit dan cephalothorax hingga telson lobster red claw dan perlakuan D (serutan) memberikan skoring peningkatan warna biru tertinggi pada capit dan cephalothorax hingga telson, yaitu masing-masing sebesar 2,82 dan 2,54. Kata kunci : lobster air tawar, warna red claw, wortel, beta karoten